Benefits of Cross-Training: Scale Development and Validity - Ninan, Navya; Roy, Joel Chacko; Thomas, Mary Rani (Prabandhan: Indian Journal of Management, 2019)
Studies related to benefits of cross-training were mainly done either in the context of qualitative research or as comprehension of desk research. The literature scarcely covered the measurement issues, and thus, it became vital to quantify and develop a scale to measure the benefits of cross-training (BCT). Cross-training means training that covers multiple tasks within a department. This training technique keeps employees prepared to handle more than a single job for which they have been initially hired. This concept is also called ’worker multifunctionality’. The study aimed to propose and validate an instrument to measure BCT. The first section of the study was exploratory factor analysis (EFA) establishing the benefits of cross-training through four dimensions namely Job Stability, Career Advancement, Networking, and Idle Time Management. Confirmatory factor analysis (CFA) was used in the second section to verify the factor structure of the observed variables. The results indicated that cross-training the employees in an organization could help practitioners to adopt the same as a strategy in retaining the employees by saving on the costs of recruitment, selection, and staffing. The findings also suggested that cross-training helped in securing a job, progressing in one’s career, enabling better interaction among the employees, and efficiently managing the idle time in the organization.